Pendidikan Karakter Di Tengah Perkembangan Teknologi: Tantangan dan Strategi Membangun Karakter Di Era Digital - Iis Susanti; Chairun Nisa Male; Okta Iwan Setiawan; Tin Amalia Fitri; Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education amid today’s rapid digital technological development has become a significant concern in the field of education. This study aims to analyze and understand the challenges of character education within technological advancement and how they can be addressed. The method employed is a literature review using a descriptive–analytical qualitative approach based on various sources related to character formation, the influence of technology, and educational strategies. The findings indicate that digital technology can serve as both an opportunity and a threat to character building, depending on how it is utilized. The main challenges include low levels of character education in the digital era, the spread of misleading information, and the decline of social interaction. Islamic-based character education, strengthened through the active roles of educators, parents, and the surrounding environment, has proven to be an effective solution in overcoming these challenges. Effective strategies include Islamic digital literacy, contextual learning approaches, and exemplary behavior demonstrated by parents and teachers. In conclusion, the challenges of character education in the midst of digital technological development require cross-sector collaboration and the wise use of technology so that Islamic values remain relevant and grounded in the lives of younger generations.